2016
DOI: 10.1136/jim-2016-000101
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin-D Status and Mineral Metabolism in Two Ethnic Populations with Sarcoidosis

Abstract: Vitamin-D insufficiency and sarcoidosis are more common and severe in African Americans (AA) than Caucasians. In sarcoidosis, substrate-dependent extrarenal 1,25-dihydroxyvitamin-D (1,25-(OH)2D) production is thought to contribute to hypercalciuria and hypercalcemia, and vitamin-D repletion is often avoided. However, the anti-inflammatory properties of vitamin-D may also be beneficial. We prospectively examined serum vitamin-D levels, calcium balance, and the effects of vitamin-D repletion in 86 AA and Caucasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 36 publications
0
22
0
1
Order By: Relevance
“…Patients who require calcium repletion are at risk for hypercalciuria and/or hypercalcemia, and need to be monitored closely, because the effects of calcium and vitamin D supplementation are complex. Studies have reported a small, but significant, increase in hypercalcemia with calcium and vitamin D supplementation (136)(137)(138), with another finding that withdrawal of calcium and vitamin D supplementation improved the hypercalcemia (127). Whereas hypercalcemia caused by vitamin D supplementation did not cause sustained renal damage, vitamin D supplementation was shown to be ineffective in terms of improved bone health or other benefits (123) Rationale for question.…”
Section: For Patients With Sarcoidosis Whomentioning
confidence: 99%
“…Patients who require calcium repletion are at risk for hypercalciuria and/or hypercalcemia, and need to be monitored closely, because the effects of calcium and vitamin D supplementation are complex. Studies have reported a small, but significant, increase in hypercalcemia with calcium and vitamin D supplementation (136)(137)(138), with another finding that withdrawal of calcium and vitamin D supplementation improved the hypercalcemia (127). Whereas hypercalcemia caused by vitamin D supplementation did not cause sustained renal damage, vitamin D supplementation was shown to be ineffective in terms of improved bone health or other benefits (123) Rationale for question.…”
Section: For Patients With Sarcoidosis Whomentioning
confidence: 99%
“…Parathormone (PTH) and Vitamin D are known to control Ca +2 and phosphate (PO 4 −2 ) homeostasis through direct actions on the PT and the DCT [53,54]. Ko and coworkers showed that PTH inhibits NCC activity via the Ras/ERK1,2 pathway [53].…”
Section: The Role Of Erk12 Signalling Along the Distal Convolute mentioning
confidence: 99%
“…Nephrolithiasis is a common renal manifestation of sarcoidosis. In a recent study, calcium in urine was higher in patients with nephrolithiasis, but serum 25-hydroxycholecalciferol and calcitriol did not correlate with urine calcium levels [16]. Coexistence of active sarcoidosis and primary hyperparathyroidism can be a diagnostic challenge, as hypercalcemia can coincide with normal or decreased parathyroid hormone values [17].…”
Section: Discussionmentioning
confidence: 99%
“…Saidenberg-Kermanac’h et al [1] in 2014 reported that low level of 25-hydroxycholecalciferol is negatively correlated with the activity of sarcoidosis. However, a recent study that compared vitamin D status and calcium metabolism in two ethnic groups of patients (Caucasian patients in Italy and African American patients in the USA) concluded that the risk of vitamin D deficiency is not increased in sarcoidosis patients in comparison with the general population, nor there was found a difference in vitamin D and calcium metabolism between the two ethnic populations [16].…”
Section: Discussionmentioning
confidence: 99%